Identification of Genes Controlled by the Essential YycFG Two-Component System Reveals a Role for Biofilm Modulation in Staphylococcus epidermidis - Xu, Tao; Wu, Yang; Lin, Zhiwei; Bertram, Ralph; Götz, Friedrich; Zhang, Ying; Qu, Di (Frontiers in Microbiology, 2017)
Biofilms play a crucial role in the pathogenicity of Staphylococcus epidermidis, while little is known about whether the essential YycFG two-component signal transduction system (TCS) is involved in biofilm formation. We used antisense RNA (asRNA) to silence the yycFG TCS in order to study its regulatory functions in S. epidermidis. Strain 1457 expressing asRNAyycF exhibited a significant delay (~4–5h) in entry to log phase, which was partially complemented by overexpressing ssaA. The expression of asRNAyycF and asRNAyycG resulted in a 68% and 50% decrease in biofilm formation at 6 h, respectively, while they had no significant inhibitory effect on 12 h biofilm formation. The expression of asRNAyycF led to a ~5-fold increase in polysaccharide intercellular adhesion (PIA) production, but it did not affect the expression of accumulation-associated protein (Aap) or the release of extracellular DNA. Consistently, quantitative real-time PCR showed that silencing yycF resulted in an increased transcription of biofilm-related genes, including icaA, arlR, sarA, sarX, and sbp. An in silico search of the YycF regulon for the conserved YycF recognition pattern and a modified motif in S. epidermidis, along with additional gel shift and DNase I footprinting assays, showed that arlR, sarA, sarX, and icaA are directly regulated by YycF. Our data suggests that YycFG modulates S. epidermidis biofilm formation in an ica-dependent manner.